Non-Tariff Measures and the World Trading System - Ederington, Josh; Ruta, Michele (World Bank, Washington, DC, 2016)
With the success of the World Trade Organization and its predecessor, the General Agreement on Tariffs and Trade, in reducing conventional tariff barriers, much of the recent focus of regional and multilateral trade agreements has switched to non-tariff measures, both border and behind-the-border policies. This paper considers the recent empirical and theoretical literature on non-tariff measures in the world trading system. It provides a set of stylized facts based on available data on non-tariff measures and reviews the key methods used to estimate their trade impact. It considers the theoretical treatment of these measures in the trade literature with a focus on the rules and institutions that govern non-tariff measures in the world trading system. It discusses some of the major issues regarding international cooperation in these policy areas, in particular whether such cooperation should entail deep integration (involving precise legally binding obligations) or shallow integration (which allows countries greater discretion in the setting of non-tariff measures). Finally, this paper reviews some of the specific features the World Trade Organization uses in dealing with non-tariff measures such as national treatment rules and non-violation complaints, and considers policy options beyond the WTO such as harmonization and mutual recognition of standards.